(untitled) (Південний архів (історичні науки), 2022)
Purpose. The aim of the article is to analyze the historiography of the Holocaust in the Kirovohrad region during 1941– 1943 and to determine the problems of future research using new documents stored in the archives of Kropyvnytskyi, but were not the subject of researchers. Methods. The regional method is used: attention is paid to the local dimension of the Holocaust in the Kirovohrad region. To analyze the patterns of behavior of the Jewish population of the region, the author uses the method of comparative analysis, comparing the attitude of Germans to Jews in 1918 and during the occupation period of 1941–1944. The method of critical analysis of works related to the events of the Holocaust in the Kirovohrad region is also used. Historiographical review is presented using the problem-chronological method, i.e. the analysis of research is offered in the context of the Holocaust in Kirovograd region. Results. The author analyzes the works of historians and historians of local lore, which contain information about the events of the Holocaust in the Kirovohrad region. It was established that the events of the Holocaust in the Kirovohrad region were considered as a separate research problem and in the context of World War II and comprehensive research on the history of the Holocaust outside the Ukraine District Commissariat and the Transnistria Governorate. Among the first group is the study of historian Vasyl Datsenko and historian Maryna Mykhailyuk, for the second group – monograph by Igor Shchupak, Andriy Kruglov and Andriy Umansky, dedicated to the Holocaust in the two above-mentioned occupation zones. The third includes works by local historians Ivan Petrenko and Oleksandr Zhosan.Little-known documents from the archives of the Kirovohrad Regional Department of the Security Service of Ukraine, which relate to the events of Kali Traf (Roma genocide) in the Kirovohrad region, are also being introduced into scientific circulation. Conclusions. Despite the historiographical work analyzed by the author of the article, the topic remains promising for further research. The materials of the article may be of interest to researchers of the Holocaust period by little-known or insufficiently developed documents by researchers, both published and those that are being introduced to scientific circulation for the first time.